On squeezed flow of couple stress nanofluid between two parallel plates - Tasawar Hayat; Rai Sajjad; Ahmed Alsaedi; Taseer Muhammad; Rahmat Ellahi (Results in Physics, 2017)
The present communication provides an analytical treatment of magnetohydrodynamic (MHD) squeezing flow of couple stress nanomaterial between two parallel surfaces. Constitutive relations of couple stress fluid are used in the problem formulation. Novel features regarding thermophoresis and Brownian motion are taken into consideration. Couple stress fluid is electrically conducted subject to time-dependent applied magnetic field. The governing partial differential system is converted into the set of nonlinear ordinary differential system through appropriate transformations. The resulting nonlinear systems have been computed through the homotopic approach. Behaviors of various sundry parameters on velocity, temperature and concentration fields are studied in detail. Further the skin friction and heat and mass transfer rates are also computed and analyzed. Keywords: Squeezing flow, Couple stress fluid, Nanoparticles, Magnetohydrodynamics